Salomon in local setting / Mohd Yusof Mohd Salleh - Mohd Salleh, Mohd Yusof (Faculty of Law, 1983)
The introduction primarily deals with the decision by the House of Lords in Salomon v Salomon and Co. It is of the writer's View that this is important so as to see and understand the Principle of corporate personality. Although the principle was stated in the 1862 Companies Act (U.K), it was not um: 1 the Salomon's case that the English Courts had full grasp of the existence of a corporate entity conferred by the Act. Chapter II of the paper deals with the application of the Principle of separate legal personality not only in English courts but also in other Commonwealth's courts. This chapter also deals with the exceptions to the general principle of separate legal personality made by the courts. Statutory provisims which admits lifting of the corporate veil is not discussed.